2014
DOI: 10.1017/s1368980013002954
|View full text |Cite
|
Sign up to set email alerts
|

Does eating family meals and having the television on during dinner correlate with overweight? A sub-study of the PRO GREENS project, looking at children from nine European countries

Abstract: Objective: Family meals have been negatively associated with overweight in children, while television (TV) viewing during meals has been associated with a poorer diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 31 publications
(57 reference statements)
0
30
2
7
Order By: Relevance
“…These results support previous literature showing a significant association between the presence of TV at family meals and lower dietary quality in children (Andaya et al, 2010; Coon et al, 2001; Feldman et al, 2007; Sweetman et al, 2011) and adults (Boutelle et al, 2003) and lower dietary meal quality (FitzPatrick et al, 2007; Fulkerson et al, 2014). Unlike a previous cross-sectional survey showing a positive relationship between TV viewing during dinner and child overweight status in 3 of 9 countries (Roos et al, 2014), a significant association between the presence of TV and child weight status was not found.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results support previous literature showing a significant association between the presence of TV at family meals and lower dietary quality in children (Andaya et al, 2010; Coon et al, 2001; Feldman et al, 2007; Sweetman et al, 2011) and adults (Boutelle et al, 2003) and lower dietary meal quality (FitzPatrick et al, 2007; Fulkerson et al, 2014). Unlike a previous cross-sectional survey showing a positive relationship between TV viewing during dinner and child overweight status in 3 of 9 countries (Roos et al, 2014), a significant association between the presence of TV and child weight status was not found.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, a study examining adolescent electronic media use during mealtimes found that more frequent media use was associated with lower family communication and lower family meal importance (Fulkerson et al, 2014). A study in nine European countries examining TV viewing during family meals and weight status found a positive association between TV viewing during dinner and child overweight status in three of the nine countries (Roos et al, 2014). While these previous studies suggest that TV viewing during family meals may reduce the protective nature of family meals, many of these studies used self-report measures, were not conducted on diverse participants, did not differentiate between having the TV on as background noise versus actively watching TV during the meal, and did not measure other important family meal variables such as the emotional atmosphere and the healthfulness of the foods offered during family meals.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the prevalence of obesity and weight-related behaviours, including the prevalence of family meals, have been found when comparing the northern and southern regions of Europe [24,25]. Participants from the nine European countries were therefore regrouped into the following three geographical regions in order to explore such differences: central (Austria, Belgium, the Netherlands), north (Denmark, Iceland, Norway, Sweden), and south (Portugal, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of family meals has been found to vary across European countries among children between the ages of 10 and 12 and is more prevalent in the northern countries than in southern and eastern countries [25]. However, data on family meals are scarce in Europe, and nationally representative data across Europe is not currently available [7,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation